Identifikasi Keberadaan Soil Transmitted Helminths pada Sayuran Lalapan di Warung Makan Grogol Petamburan - Susanto, Inneke Kusumawati; Pasaribu, Donna Mesina Rosadini; Suhandi, Priska Yoverani (Jurnal Kedokteran Meditek, 2025)
Introduction: Soil Transmitted Helminths (STH) infection is a worm infection through the soil. Consumption of raw food such as fresh vegetables is a route of STH transmission to humans because soil is a growth medium for vegetables and an ideal place for worm development into an infective form so that there is a risk of contamination when the soil is contaminated with human feces containing worm eggs. Transmission through the use of vegetable fertilizers contaminated with human feces, vegetables that are not washed properly and poor food management. Research on STH eggs in fresh vegetables in Grogol Petamburan food stalls has never been conducted. Objective: The study aims to determine the presence or absence of STH, the prevalence of contamination, stages and types of STH eggs in fresh vegetables in Grogol Petamburan food stalls to provide the public with information to pay attention to the cleanliness of fresh vegetables. Method: The study was descriptive with microscopic examination using the sedimentation method. The sampling technique was a total sampling of 84 fresh vegetables samples taken from 38 Grogol Petamburan food stalls. Fresh vegetables samples, namely cabbage, lettuce and basil, were examined in the parasitology laboratory. Data on hygiene and sanitation practices were taken from interviews. Results: STH identification results in 9 samples (10.7%) were positive for STH contamination. Ascaris lumbricoides eggs were found in the contaminated samples, while Trichuris trichiura and Hookworm were not found. Conclusion: Based on the results of the study, the samples were positive for STH contamination in the Ascaris lumbricoides egg stage. The results indicate that the raw vegetables are not suitable for consumption.